2019
DOI: 10.1097/gme.0000000000001363
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavior therapy for menopausal symptoms (CBT-Meno): a randomized controlled trial

Abstract: Objective: To evaluate the effectiveness of cognitive behavioral therapy for menopausal symptoms (CBT-Meno) compared with a waitlist condition (no active intervention). A randomized controlled trial was conducted with 71 perimenopausal or postmenopausal women who were seeking treatment for menopausal symptoms. Methods: Blind assessments were conducted at baseline, 12 weeks postbaseline, and 3 months post-treatment. An intention-to-treat analysis was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 43 publications
4
44
0
Order By: Relevance
“…The findings were in line with Jalal et al [ 76 ] which provided evidence of the effectiveness of CA-CBT among the Muslim population in Egypt, and in line with Zakaria and Akhir [ 75 ] for the Malaysian population. Also, these findings are consistent with that of prior studies that suggested depression will often improve following CA-CBT intervention [ 5 , 76 , 77 , 78 , 79 , 80 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The findings were in line with Jalal et al [ 76 ] which provided evidence of the effectiveness of CA-CBT among the Muslim population in Egypt, and in line with Zakaria and Akhir [ 75 ] for the Malaysian population. Also, these findings are consistent with that of prior studies that suggested depression will often improve following CA-CBT intervention [ 5 , 76 , 77 , 78 , 79 , 80 ].…”
Section: Discussionsupporting
confidence: 90%
“…Thus, cognitive distortion as the component of false beliefs and assumptions was distinctly emphasized. Apart from that, it was found that in addition to depressive symptoms, women's sexual functions were largely influenced by a lack of social skills, such as assertiveness, and problem-solving appraisal, which could affect the severity of depression, which is in line with the study by Peleg-Sagy and Shahar [84] and Green et al [79]. The treatment protocol was adjusted to meet the participants' needs as a Muslim woman, as in the study conducted by Zakaria and Akhir [75].…”
Section: Discussionsupporting
confidence: 80%
“…There was good compliance and CBT intervention was considered to be acceptable and feasible for women with psychological disorders. Using a different protocol (CBT‐Meno), Green et al ( 2019 ) evaluated a 12‐session CBT group‐based treatment for women who had both problematic VMS and moderate to severe depressed mood in an exploratory trial with significant reductions in VMS interference and bother, and in self‐reported depressive symptoms at 3‐month follow‐up.…”
Section: Figurementioning
confidence: 99%
“…Psychological therapy, specifically Cognitive Behavioral Therapy (CBT), has been proposed as a low-risk treatment for menopausal symptoms with studies showing CBT as effective in reducing several common menopausal symptoms [e.g., vasomotor symptoms, depression, anxiety, and sleep difficulties; (17)(18)(19)]. Sexual concerns, however, have either not been directly targeted at all in current CBT protocols, or the two protocols that have included sessions on sexual concerns (19,20), have only demonstrated modest gains in a single domain (e.g., sexual desire).…”
Section: Introductionmentioning
confidence: 99%
“…Psychological therapy, specifically Cognitive Behavioral Therapy (CBT), has been proposed as a low-risk treatment for menopausal symptoms with studies showing CBT as effective in reducing several common menopausal symptoms [e.g., vasomotor symptoms, depression, anxiety, and sleep difficulties; (17)(18)(19)]. Sexual concerns, however, have either not been directly targeted at all in current CBT protocols, or the two protocols that have included sessions on sexual concerns (19,20), have only demonstrated modest gains in a single domain (e.g., sexual desire). Further, most CBT studies for menopause have included broad measures of menopausal symptoms (e.g., the Greene Climacteric Scale, Menopause Rating Scale), which do not allow us to determine the impact of CBT on important domains of sexual functioning and satisfaction specifically sexual desire, interest, and self-image.…”
Section: Introductionmentioning
confidence: 99%